Auditoría del rubro anticipos a proveedores – cuentas por pagar proveedores de una empresa industrial del sector agrícola “perla del pacífico”, ubicada en la ciudad de Guayaquil al 31 de diciembre del 2008 - Falconí Anzules, Vicente (2009)
The auditory on the Financial Statements performs great importance for the control of the items of a company or institution. This work consists of realizing an audit in the financial statements in the accounts of Advance payments to Suppliers and Accounts to pay Suppliers of a company of the industrial sector, dedicated to the development of agricultural activities as far as the purchase, sale and export of these products. Also realizing an audit test for the item significant Advance payments to Suppliers and Accounts To pay Suppliers, respect the rotation of business of the company. In the first chapter we have developed the theoretical mark, in the second chapter to embrace the audit focus. For the development on the same we make a brief description of the knowledge for the business, we determine analytic procedures and preliminary as well as the applications of statistical techniques, the global ands planned materiality was calculated as the application of the components of the internal control. In the third chapter realized audit test for the item Advance payments to Suppliers and Accounts to pay Suppliers, these tests allow us to determine significant discoveries and to verify the execution of controls. For each test we describe their objective, procedure and condition. In the fourth chapter contains the conclusions and recommendations as soon as if the balances are reasonable or not.